Determining Factors of Asset Misappropriation Tendency by Employees in Perspective of Fraud Hexagon Theory - Farlina Wahyulistyo; Nur - Cahyonowati (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
AbstractPurpose: This study aims to provide empirical evidence and analyze factors that contribute to asset misappropriation by employees through the fraud hexagon theory perspective. The theory consists of six components that trigger fraud, such as stimulus (incentives), opportunities, rationalization, capabilities, ego, and collusion. In this study, the stimulus factor is divided into financial and non-financial (job pressure).Method: The study obtains data by distributing questionnaires to 218 participants employees from 5 departments of XTZ Hospital in Semarang. Only those who work in structural and functional positions are the participants, considering they are responsible for the hospital asset management. To collect data, this study implements a proportional stratified random sampling method, and test the hypothesis by using the 7.0 version of WarpPLS analysis tool.Findings: The results indicate that financial pressure, opportunity, capability, ego, and collusion influence asset misappropriation. Meanwhile, non-financial pressure (job pressure) and rationalization do not contribute to misappropriation.Novelty: This research implies an overview of why the management has to carefully review the factors that lead to asset misappropriation in the workplace. Besides, these can be used for formulating guidelines to prevent misappropriation. Keywords: Financial pressure, fraud hexagon theory, asset misappropriation